2008
DOI: 10.1093/bioinformatics/btn267
|View full text |Cite
|
Sign up to set email alerts
|

Gain and loss of phosphorylation sites in human cancer

Abstract: In this study, we investigate the role of phosphorylation in somatic cancer mutations and inherited diseases. Somatic cancer mutation datasets were shown to have a significant enrichment for mutations that cause gain or loss of phosphorylation when compared to our control datasets (putatively neutral nsSNPs and random amino acid substitutions). Of the somatic cancer mutations, those in kinase genes represent the most enriched set of mutations that disrupt phosphorylation sites, suggesting phosphorylation targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 34 publications
5
86
0
Order By: Relevance
“…Protein kinases and phosphatases are global regulators of protein activity, and their dysfunction or aberrant activation results in a wide spectrum of diseases including cancers (33,34). Cancers are widely characterized by abnormal activation of protein kinases such as Akt, tyrosine kinase, casein kinase, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Protein kinases and phosphatases are global regulators of protein activity, and their dysfunction or aberrant activation results in a wide spectrum of diseases including cancers (33,34). Cancers are widely characterized by abnormal activation of protein kinases such as Akt, tyrosine kinase, casein kinase, etc.…”
Section: Discussionmentioning
confidence: 99%
“…These modifications thereby translate the modification of the target protein into biological action by affecting the interaction between their targets and other cellular factors or proteins [52]. Mutations in the post translational target sites leading to gain or loss of the PTMs may be involved in the human diseases [53,54]. We investigated the putative PTM sites in the PCNA protein and found that Serine at 39 th position was a recognizable phosphorylation site whereas lysine at 248 th position was the putative acetylation site.…”
Section: Discussionmentioning
confidence: 99%
“…However, nonsilent mutations, which include missense, nonsense, insertions, deletions, and mutations affecting splicing, are not all functionally equivalent, and as several groups have found, not equally selected for (Radivojac et al 2008;Mort et al 2010;Fischer et al 2011;Youn and Simon 2011). For example, mutations introducing stop codons (nonsense), those affecting splicing, or resulting in functional alterations to phosphorylation sites occur at significantly higher rates than other non-silent mutations, which may signify their selection and importance to cancer cells (Greenman et al 2006;Radivojac et al 2008;Fischer et al 2011;Youn and Simon 2011). Moreover, mutations occurring in a tumor sample with very few mutations overall, compared with a tumor sample with thousands, are likely relevant to tumor biology (Youn and Simon 2011).…”
Section: Deciphering Biologically Relevant Dna Mutationsmentioning
confidence: 99%